Influence of strength and plyometric program on accleration speed in 14-15 years old hockey players at 5 m distance on-ice and off-ice - Knechta, M.; Cillik, I. (International Journal of Physiology, Nutrition and Physical Education, 2021)
The aim of our study was to find out the effect of strength and plyometric excercises using acceleration speed on-ice and off-ice at a distance of 5 meters in ice hockey players during the regular season. The research set consisted of 33 players (Male; age: 14.7 ± 0.7; height: 166.5cm ± 7.3; weight: 53.4kg ± 6.9) divided into two grup. Experimental group (n=18) and control group (n=15). During 8 weeks, the players in experimental group performed 4-5 training units on-ice, two training units off-ice, one match and +2 extra strength and plyometric units off-ice from 20 to 30 minutes before training units on-ice. Players from control group performed the same training units without +2 extra strength and plyometrical units off-ice from 20 to 30 minutes before training units on ice. Speed diagnostics consisted of the following one tests on-ice and one tests off-ice. We used two-way ANOVA and effect size theory to process the statistical data. The results show that between Pretest1 and Posttest1 in the experimental group, an effect size was demonstrated in tests 5 on-ice (d = 0.53) medium. Between Pretest1 and Posttest2 in the experimental set, the effect size was (d = 0.38) small. Off-ice test in experimental group shows small effect size (d = 0.25) between Pretest1 and Postest1 and deterioration between Pretest1 and Postest2. Results in control group on-ice shows that between Pretest1 and Postest1 effect size is (d = 0) trivial (stagnation) and between Pretest1 and Postest2 deterioration. Off-ice test in control group shows small effect size (d = 0.26) between pretest1 and Postest1 and deterioration between Pretest1 and Postest2. The results of the quasi-experiment showed that the influence of strength and plyometric exercises on the improvement of the level of running and skating speed of the players of the experimental group was proven.